CHALLENGES AND OPPORTUNITIES FOR RURAL ENTREPRENEURSHIP - Tanwar, Dr. Samridhi; Bhardwaj, Ms. Surbhi (The journal of contemporary issues in business and government, 2022)
Entrepreneurship is an area that has attained importance in today’s era. Entrepreneurship is a key component of India’s 2020 strategy for sustainable, smart, and inclusive growth as 75 percent of the population residing in villages is still involved in agriculture and allied activities. Government alone can’t generate employment opportunities for villagers. Thus, individuals are welcomed and promoted to undertake the entrepreneurial task in rural areas. Rural entrepreneurship not only generates employment opportunities but also puts a check on the migration of youth towards urban areas. Through efficient and effective utilization of national resources, rural entrepreneurs act as catalysts for economic development and agents of social transformation and change. Enormous opportunities are available in rural industrialisation, if a person is passionate about being an entrepreneur. Though challenges like family, finance, poor infrastructure, mall culture are there in the path of rural entrepreneurship self-motivation and feel of personal achievement can make every dream a possible thing.